Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1079/ssr2003149
|View full text |Cite
|
Sign up to set email alerts
|

Onset of germinability, desiccation tolerance and hardseededness in developing seeds of Peltophorum pterocarpum (DC) K. Heyne (Caesalpinioideae)

Abstract: In the hot and dry conditions in which seeds of the tree legume Peltophorum pterocarpum develop and mature in Vietnam, seed moisture content declined rapidly on the mother plant from 87% at 42 d after flowering (DAF) to 15% at 70 DAF. Dry weight of the pods attained a maximum value at about 42 DAF, but seed mass maturity (i.e. the end of the seed-filling phase) occurred at about 62 DAF, at which time seed moisture content was about 45-48%. The onset of the ability of freshly collected seeds to germinate (in 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…15 % in Peltophorum pterocarpum (Mai-Hong et al 2003), 12 % in Gleditsia triacanthos (Geneve 2009), G. aquatica (Geneve 2009), Gymnocladus dioicus (Geneve 2009), Lupinus arboreus (Hyde 1954), Trifolium ambiguum (Hay et al 2010), T. pretense (Hyde 1954) and T. repens (Hyde 1954), 11 % in L. digitatus (Gladstones 1958) and Geranium carolinianum (Gama-Arachchige et al 2011). However, the reason why some seeds develop impermeable coats, while others maturing on the same plant produce permeable seed coats remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…15 % in Peltophorum pterocarpum (Mai-Hong et al 2003), 12 % in Gleditsia triacanthos (Geneve 2009), G. aquatica (Geneve 2009), Gymnocladus dioicus (Geneve 2009), Lupinus arboreus (Hyde 1954), Trifolium ambiguum (Hay et al 2010), T. pretense (Hyde 1954) and T. repens (Hyde 1954), 11 % in L. digitatus (Gladstones 1958) and Geranium carolinianum (Gama-Arachchige et al 2011). However, the reason why some seeds develop impermeable coats, while others maturing on the same plant produce permeable seed coats remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Mai-Hong et al (2003) reported that hardseededness began to be induced when Peltophorum pterocarpum seeds were dried to about 15% moisture content and below, with a negative Relationship between seed moisture content (mc, %, f. wt.)…”
Section: Resultsmentioning
confidence: 99%
“…This equation has already been applied to forest species (Dickie et al, 1990;Medeiros et al, 1998;Bonner, 1999;Chaves & Usberti, 2004). However, viability constants are specific for each species and therefore must be determined for each species of economic, ecological and scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…The development of seeds (or fruits) with PY has been described for Rhus aromatica and Rhus glabra (Anacardiaceae) (Li et al . 1999); several Fabaceae species, including Peltophorum pterocarpum (Mai‐Hong et al . 2003); Bixa orellana (Bixaceae) (Yogeesha et al .…”
Section: Introductionmentioning
confidence: 99%